FEMINISME DALAM SERIAL SOFIA THE FIRST EPISODE JUST ONE PRINCESS - Clarisa Putri Siswanti (Jurnal Bastra (Bahasa dan Sastra), 2024)
Cartoon or series can be used as a means of conveying learning or addressing issue that occur in the community. One children’s series that addressing feminist issues is the cartoon produce by Walt Disney, namely Sofia The First in episode ‘Just One Princes.’ Sofia as the main female protagonist fights for her rights as she belittled by her friends, who believe that women can’t engage in activities typically associated with men. In this study, the author utilizes the feminist theory presented by Goldman, as well as descriptive analysis methods and note taking techniques to gather and analyze the data. Based on the analysis, it can be concluded that this cartoon exhibits four (4) classifications of gender discrimination experienced by Sofia: Marginalization, labeling, subordination, and violence.